A descentralização da educação no Maranhão: processos determinantes e impactantes na reforma da educação básica no período de 1998 a 2002 - Silva, Márcia Valéria Melo e (2015)
This study exposes the analysis about THE DECENTRALIZATION OF EDUCATION IN MARANHÃO: determinants and impacts on the process of reform of basic education in the period from 1998 to 2002. Expatiate about the reform of Brazilian state from the historical aspects who outlined the Brazilian educational policy, highlighting the state reform from the Neoliberal context and the conceptual and historical (re)configurations of educational policies in Brazil. Expose on the research the change that occurred since the Master Plan of the Reform of the State Apparatus, in the first presidential term of Fernando Henrique Cardoso. Examines, the insertion of Maranhão since the state reform and the educational changes since this reforms. the reconfigurations of educational policy in the Brazilian society and the particular aspects of basic education in Maranhão, finaly, giving empashis to the historical, socioeconomic and political contexts in that manage the programs and projects of municipalization and decentralization; and some challenges of the process of implementation of this projects on the basic education in Maranhão